PENGAMALAN ZAKAT PROFESI DI KOTA BANJARMASIN - Nahdhah Nahdhah; Indah Dewi Megasari (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This research aims to study the percentage of profession zakat (purification/ support of the needy) in Banjarmasin. Theoretically, it is also expected to enrich the Islamic knowledge particularly in the field of Islamic social jurisprudence practice.This field research focuses on the zakat givers (professionals) living in Banjarmasin, and studies some cases of any professions. In further, by qualitative approach the research gains data to build a deep understanding of zakat givers experiences in calculating their percentage of zakat.The percentage which is due on gold, silver and cash funds that have reached the amount of 85 grams of gold and held in possession for one lunar year is two and a half percent.A person may also give as much as he or she pleases as voluntary charity to muzakki ‎(the needs), or through the legal institution.